Do Capital and Business Volume Matter for Productivity of the Cooperatives in Indonesia? - M. Shabri Abd. Majid; Azhari Azhari; Faisal Faisal; Heru Fahlevi (Bina Nusantara University, 2020)
This research explored and analyzed the determinants of productivity of the cooperatives in Indonesia. These determinants included own capital, external capital, and business volume. The aggregate data of cooperatives were at the provincial level across 33 provinces in Indonesia. The data were gathered from the report of the Kementerian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia (Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia) over the 2010-2015 period. The data were analyzed using the panel regression technique. The result shows that own capital and business volume have a significant positive effect on the productivity of cooperatives. However, external capital has an insignificant effect on the productivity of cooperatives. To further improve their productivity, the cooperatives should increase the capital from internal sources as well as their business volume through more diversified business activities.